THE EFFECT OF AUTOGENIC RELAXATION THERAPY AND CONSUMPTION OF AMBON BANANAS ON REDUCING BLOOD PRESSURE IN HYPERTENSION PATIENTS IN THE ELDERLY IN THE KUALA LEMPUING PUBLIC HEALTH CENTER AREA IN BENGKULU CITY - Agung Riyadi; Sachiazahra Balqis; Hermansyah Hermansyah (Poltekkes Kemenkes Bengkulu, 2023)
Hypertension is a condition where sufferers experience an increase in blood pressure which results in morbidity and mortality.2018 Riskesdas data shows that the prevalence of hypertension in Indonesia is 34.1%. Hypertension in Indonesia is increasing every year with a prevalence in Bengkulu Province of 28.14% and a prevalence of hypertension in the elderly in Bengkulu City of 2.45%.(RI Ministry of Health, 2018). The aim of this research is to determine whether there is an effect of autogenic relaxation therapy and consumption of Ambon bananas on reducing blood pressure in elderly hypertensive sufferers in the Kuala Lempuing Community Health Center Working Area. This type of research isquasi experimentalWith the research design used pretest-posttest with control group, the sample was elderly people with hypertension in the working area of ??the Kuala Lempuing Public Health Center, totaling 42 people using a purposive sampling technique. Data analysis in this study was carried out using the Mann-Whitney test to see differences between the intervention and control groups and the Wilcoxon signed ranks test to see differences before and after treatment. The research results show thatThere was a decrease in mean systolic blood pressure3.95mmHgand diastolic4.67mmHgin the Intervention group and a decrease in mean systolic blood pressure1.81mmHgand diastolic2.47 mmHg in the control group. There was an effect of autogenic relaxation therapy and consumption of Ambon bananas (p=0.000) on systolic and diastolic blood pressure in the elderly.